2015
DOI: 10.1007/s00128-014-1452-x
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Concentrations in Fishes from Juru River, Estimation of the Health Risk

Abstract: This study examined the concentration of heavy metals in 13 fish species. The results indicated that shellfish species (clams) have the highest metal concentrations, followed by demersal and pelagic fishes. The mean concentration of metals in clams are Zn 88.74 ± 11.98 µg/g, Cu 4.96 ± 1.06 µg/g, Pb 1.22 ± 0.19 µg/g, Cd 0.34 ± 0.04 µg/g dry wt. basis, whereas the same measure in fish tissues was 58.04 ± 18.51, 2.47 ± 1.21, 0.58 ± 0.27 and 0.17 ± 0.08 µg/g dry wt. basis. The concentrations of heavy metals in cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 10 publications
1
17
1
1
Order By: Relevance
“…The THQ findings for the general population in the present study were in contrast with those reported for Pb and Cd (Idriss & Ahmad, 2015) in Malaysia and also for Hg (Storelli & Barone, 2013) in Italy, where the THQ values were above 1, suggesting a health risk from the consumption of fish collected from these areas of studies. On the other hand, THQ values of less than 1.0 for adults were reported for Cd, Pb, and Hg in fish from the Mediterranean Sea (Copat et al, 2012) and also for As, Cd, and Pb in marine wild fish from China (Zhang & Wang, 2012), and they concluded that there was insignificant health risk.…”
contrasting
confidence: 99%
“…The THQ findings for the general population in the present study were in contrast with those reported for Pb and Cd (Idriss & Ahmad, 2015) in Malaysia and also for Hg (Storelli & Barone, 2013) in Italy, where the THQ values were above 1, suggesting a health risk from the consumption of fish collected from these areas of studies. On the other hand, THQ values of less than 1.0 for adults were reported for Cd, Pb, and Hg in fish from the Mediterranean Sea (Copat et al, 2012) and also for As, Cd, and Pb in marine wild fish from China (Zhang & Wang, 2012), and they concluded that there was insignificant health risk.…”
contrasting
confidence: 99%
“…Namun, berdasarkan data dalam Tabel 1 dan 2 tampak bahwa konsentrasi logam berat Fe, Cd dan Pb dalam jaringan otot ikan nila yang dipelihara di kolam pasca tambang batubara jauh lebih tinggi di dalam badan perairannya.Logam berat Pb dan Cd dalam air umumnya berbentuk ion dan logam. Logam tersebut masuk ke tubuh ikan secara langsung atau tidak langsung( melalui membran insang, kulit, lapisan mukosa, makanan tidak langsung dari organisme lain seperti ikan kecil, invertebrata, dan vegetasi air, yang kemudian diangkut darah ke seluruh tubuh kemudian terakumulasi di dalam beberapa organ, salah satunya daging ikan (Polatmet al, 2015).Namun, akumulasi ini tergantung pada asupan, penyimpanan, dan eliminasi dari tubuh.Hal ini berarti logam yang memiliki serapan tinggi dan eliminasi rendah tingkat dalam jaringan ikan diperkirakan akan terakumulasi ke tingkat yang lebih tinggi [Idriss et al,2015).…”
Section: Hasil Logam Berat DI Badan Perairan Dan Ikanunclassified
“…Though, this bioaccumulation relies on their intake, storage, and elimination from the body [2]. This indicates that subjected to high uptake and low elimination rates within fish tissues could become stored at higher concentrations [10]. Fish uptake heavy metals via the ingestion of contaminated food by GIT or gills and skin [11].…”
Section: Introductionmentioning
confidence: 99%